Srikandi Heroin Discourse in Online News Framing Female Ministers of Indonesia - Dewi Sad Tanti Dewi Sad Tanti (Jurnal Spektrum Komunikasi, 2022)
This research is intended to mapping the depiction of the female minister as public officials in Indonesia. Through this research, it is expected to find out how the media package the character of female minister base on announced the composition of ministers in the cabinet. This research uses the framing framework developed by Robert N. Entman. This model is used to describe the selection process and highlight certain aspects of reality by the media. Framing Entman. Define Problems; How can Female Minister problems become an issue? How Economic Nation Impact form Female Minister? Or as a problem?, Diagnose Causes ; What is the reason for being called an female minister figure? What is considered the cause of a problem?, Make Moral judgement ; What moral values are presented to explain. What moral values are used to legitimize an female minister? and the last Treatment Recommendation , What solutions are offered to address female minister? What path is offered and main opinion to Female Minister? . Result of this research are Indonesia Online Media Online Media Frame 5 Female Ministers in Indonesia can be put together, the confirmation of women's success as leaders up to 2x is from the role of the family, the criteria for a leader to be trusted as a minister, trustworthy, competent and qualified in their field, in accordance with community support, supported by predecessor ministers , depicted like Heroine.